Could Ageing-Related Chronic Skin Problems be Attributed to Neuronal and Non-Neuronal Dysfunctions? - Pierre A Guertin (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2016)
The International League of Dermatological Societies (ILDS) has identified the consequences of skin ageing as one of the most important challenges in global skin health. As we get older, the skin undergoes indeed significant changes - many of which may be attributed to systemic, metabolic, hormonal and neuronal changes. As any other organ of the body, the skin is constituted of cells and systems that are, under physiological conditions, controlled by signals arising from the central, peripheral and autonomous nervous systems. Thus, several central nervous system (CNS) and non-CNS-mediated diseases and dysfunctions may lead secondarily to skin problems. The next-generation drugs and therapeutics for skin diseases will probably be increasingly acting upon central and peripheral mechanisms for superior efficacy which, in turn, shall force regulatory authorities to impose stricter regulations prior to approval of dermatological products.